Honey, Propolis, and Royal Jelly: A Comprehensive Review of Their Biological Actions and Health Benefits - Pasupuleti, Visweswara Rao; Sammugam, Lakhsmi; Ramesh, Nagesvari; Siew, Hua Gan (Hindawi Publishing Corporation, 2017)
There are several health benefits that honeybee products such as honey, propolis, and royal jelly claim toward various types of diseases in addition to being food. Scope and Approach. In this paper, the effects of honey, propolis, and royal jelly on different metabolic diseases, cancers, and other diseases have been reviewed. The modes of actions of these products have also been illustrated for purposes of better understanding. Key Findings and Conclusions. An overview of honey, propolis, and royal jelly and their biological potentials was highlighted. The potential health benefits of honey, such as microbial inhibition, wound healing, and its effects on other diseases, are described. Propolis has been reported to have various health benefits related to gastrointestinal disorders, allergies, and gynecological, oral, and dermatological problems. Royal jelly is well known for its protective effects on reproductive health, neurodegenerative disorders, wound healing, and aging. Nevertheless, the exact mechanisms of action of honey, propolis, and royal jelly on the abovementioned diseases and activities have not been not fully elucidated, and further research is warranted to explain their exact contributions.